1999
DOI: 10.1016/s0014-5793(99)00711-5
|View full text |Cite
|
Sign up to set email alerts
|

Permutation of modules or secondary structure units creates proteins with basal enzymatic properties

Abstract: The RNase activity of barnase mutants obtained by the permutation of modules or secondary structure units was investigated. Four of the 45 mutants had weak but distinct RNase activity, and they had unique optimum pHs and temperatures like natural enzymes. One of the active mutants had an ordered conformation, but the others did not. An active mutant having disordered conformation formed an ordered conformation in the presence of GMP, which is an inhibitor of this mutant. These results indicate that the amino a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2001
2001
2006
2006

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…In our previous paper (20,34), the foldability and RNase activity of 45 barnase mutants obtained by the permutation of modules or secondary structure units were investigated. This study suggests that amino acids not involved directly in catalysis in foldable proteins have been selected as scaffolds to stabilize the active site with appropriate conformations in the course of globular protein evolution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous paper (20,34), the foldability and RNase activity of 45 barnase mutants obtained by the permutation of modules or secondary structure units were investigated. This study suggests that amino acids not involved directly in catalysis in foldable proteins have been selected as scaffolds to stabilize the active site with appropriate conformations in the course of globular protein evolution.…”
Section: Discussionmentioning
confidence: 99%
“…This study suggests that amino acids not involved directly in catalysis in foldable proteins have been selected as scaffolds to stabilize the active site with appropriate conformations in the course of globular protein evolution. The mutant having a nascent active site, but not a stable scaffold, can be considered as globular protein in an 'evolutionarily intermediate state' (34). Theoretical studies have successfully simulated the trajectory in which evolution of stability around the active site leads to a sequence which folds globally into a conformation (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…The RNase activity of the 46 barnase mutants was also investigated, and we found that eight secondary structure unit mutants and two module mutants had weak but distinct RNase activity [30,31]. RNase activity of several of the mutants was further investigated at different pHs, and we found that they each showed a bell-shaped curve with an optimum pH.…”
Section: Enzymatic Activitymentioning
confidence: 90%
“…On the other hand, because S4523 does not have such a stable conformation, the overall structure of the mutant would be easily affected by conformational change of the active site. Amino acids that are not involved directly in the activites would have been selected as scaffolds to generate active sites with thermal stability in the early stages of globular protein evolution [31,33,34]. If this is the case, the barnase mutants that have an active site, but not a stable scaffold can be considered as globular proteins in evolutionarily intermediate states.…”
Section: Evolutionarily Intermediate States On the Fitness Landscapementioning
confidence: 99%
“…A commonly accepted view is that new folds are pieced together from small parts of existing folds. 32,33,39,40 But to the extent that a new fold is really new, its formation must require the joint solution of at least a considerable number of new local stabilization problems of the kind described above. How likely is it that sequences that carry the hydropathy signatures of other folds and provide joint solutions to the stabilization problems for those folds may be pieced together in such a way that they satisfy a new set of constraints, equally demanding but substantially different?…”
Section: Estimating the Prevalence Of Functional Proteinsmentioning
confidence: 99%